Conversion by Infection: The Sociophobic of Cults in The Omega Man - Laycock, Joseph P. (International journal for the study of new religions, 2010)
The Omega Man (1971), starring Charlton Heston, is a film adaptation of the book I Am Legend by Richard Matheson. Matheson’s novel tells the tale of Robert Neville, the last man left alive after germ warfare has infected humanity with vampirism. The Omega Man differs from the original novel and its other adaptations in several ways: The most notable is that it imbues Heston’s character with obvious Christ-like symbolism. A more significant change went largely unnoticed: instead of vampires, those infected with the plague become part of a militant group called "The Family." Although The Family is never overtly described as a religion, the antagonists speak to a popular fear of new religious movements that emerged in the 1960s. By pitting a medicalized Christ against a disease-like religion, The Omega Man helped to engender a dual perspective of deviant religion as simultaneously medical and heretical. This dual perspective would shape the discourse of the "cult wars in the United States for decades, from the abductions carried out by cult "deprogrammers" to the siege of the Branch Davidian compound in Waco, Texas.